Fundamentals of heat engines - Ghojel, J. I. (Wiley-ASME series in mechanical engineering, 2020)
"Fundamentals of Heat Engines comprehensively covers heat engine cycles with gradual increase in degree of complexity from ideal (theoretical) cycles followed by practical cycles then real cycles. To facilitate the transition from one type of cycle to another, additional material is introduced covering fundamental engineering science principles in mechanics, fluid mechanics, thermodynamics and thermochemistry. The content is designed in such a way that it can be customized by instructors to suit beginner or advanced undergraduate courses and entry level postgraduate studies in automotive, mechanical and aerospace degrees. It is also an excellent reference for engineers working in this area"--